2015
DOI: 10.1155/2015/293163
|View full text |Cite
|
Sign up to set email alerts
|

Use of Contrast-Enhanced Ultrasound in Carotid Atherosclerotic Disease: Limits and Perspectives

Abstract: Contrast-enhanced ultrasound (CEUS) has recently become one of the most versatile and powerful diagnostic tools in vascular surgery. One of the most interesting fields of application of this technique is the study of the carotid atherosclerotic plaque vascularization and its correlation with neurological symptoms (transient ischemic attack, minor stroke, and major stroke) and with the characteristics of the “vulnerable plaque” (surface ulceration, hypoechoic plaques, intraplaque hemorrhage, thinner fibrous cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 32 publications
0
27
0
3
Order By: Relevance
“…Consistent with these ndings, hypoechoic plaques tend to have more vulnerable pathologic features, abundant lipids, and hemorrhage and are associated with an increased risk of cerebrovascular events [32]. Varetto et al reported a statistically signi cant correlation between increased vascularization of carotid atherosclerotic plaques evaluated by CEUS and cerebrovascular neurological events [30]. Similarly, Wu et al concluded that strong contrast enhancement can reveal culprit lesions, likely suggesting greater neovascularization and/or in ammatory activity in atherosclerotic lesions [36].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Consistent with these ndings, hypoechoic plaques tend to have more vulnerable pathologic features, abundant lipids, and hemorrhage and are associated with an increased risk of cerebrovascular events [32]. Varetto et al reported a statistically signi cant correlation between increased vascularization of carotid atherosclerotic plaques evaluated by CEUS and cerebrovascular neurological events [30]. Similarly, Wu et al concluded that strong contrast enhancement can reveal culprit lesions, likely suggesting greater neovascularization and/or in ammatory activity in atherosclerotic lesions [36].…”
Section: Discussionmentioning
confidence: 78%
“…Unstable atherosclerotic carotid plaques are particularly vulnerable to rupture, which is induced by the loss of thin brous cap integrity, strong intraplaque in ammatory reaction, and luminal blood communication with the thrombogenic core of the plaque. [29,30] Thrombogenic material is diffused into circulation after plaque rupture, thereby occluding the intracranial cerebral arteries and resulting in ischemia of cortical and subcortical brain tissue. However, identi cation of vulnerable atherosclerotic plaques in patients poses a signi cant clinical challenge.…”
Section: Discussionmentioning
confidence: 99%
“…However, CEUS is not commonly used in routine practice yet, so there is no consensus on which quantitative parameters could discriminate between a ''stable'' and an ''unstable'' plaque, also because different machines and softwares are used. 9 In a previous work by our institution, 8 we used SI mean and SI maximum as parameters of blood perfusion in a ROI of the plaque detected at CEUS examination. We found a correlation between high values of SI mean and SI maximum (> 20 and > 26, respectively) and DW-MRIedetected cerebral microembolization after CAS.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers [6][7][8] have reported that the main sources of cerebral microemboli are the extracranial and intracranial arteries and that an atherosclerotic carotid artery is the most common source. Therefore, in ultrasonic research, the carotid is the most common window through which the relevant factors for stroke are investigated [14,15] . The members of our study group performed numerous investigations [10] on the microvascular distribution of carotid plaques; they also explored the microvascular distribution of carotid plaques in patients who are at risk of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%